PENGARUH PERENCANAN ANGGARAN DAN PELAKSANAAN KEGIATAN TERHADAP REALISASI ANGGARAN DI PEMERINTAH DAERAH KABUPATEN GORONTALO - Radjak, Lukfiah Irwan; Humolungo, Ferawati (Program Studi Akuntansi, 2022)
This research was conducted at the Gorontalo Regency Finance Agency. The purpose of this study was to determine the effect of budget planning on budget realization and to determine the effect of activity implementation on budget realization. This study uses quantitative methods, namely multiple linear regression formulas, coefficient of determination, F test and T test. Based on the results of the analysis, the tcount value for the budget planning variable is 3.018 when compared with the ttable value of 2.109, it can be concluded that budget planning has a positive and significant effect. on budget realization and for the activity implementation variable, the tcount value is 1.700, the ttable value is 2.109, it can be concluded that the implementation of activities has an insignificant positive effect on budget realization. So the most dominant influence on budget realization is the planning variable, so it can be concluded that budget planning and implementation joint activities have a positive and significant impact on budget realization in the Gorontalo Regency Government in 2015-2019